2017
DOI: 10.3390/ijms18091861
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of GLP-1 Receptors in DNA Repair: Implications in Neurological Disorders

Abstract: Glucagon-like peptide-1 (GLP-1) is originally found as a metabolic hormone (incretin) that is able to regulate blood-glucose levels via promoting synthesis and secretion of insulin. GLP-1 and many analogues are approved for treatment of type II diabetes. Accumulating results imply that GLP-1 performs multiple functions in various tissues and organs beyond regulation of blood-glucose. The neuroprotective function of GLP-1 has been extensively explored during the past two decades. Three of our previous studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 156 publications
(184 reference statements)
0
9
0
Order By: Relevance
“…Apart from their predominant localization in the pancreas, GLP‐1 receptors (GLP‐1R) are also present in the brain regions including but not limited to the frontal cortex, hippocampus, amygdala, dorsal raphe, thalamus, hypothalamus, and the cerebellum. Also, caudal brainstem neurons protruding to the hippocampus, cortex, and hypothalamus have been found to secrete GLP‐1 (Merchenthaler et al., 1999; Yang et al., 2017). This extra‐pancreatic localization of the GLP‐1R suggests its prospect of employment in the combat against neurological diseases, including depression.…”
Section: Physiological Factors That Play Key Roles In the Comorbiditymentioning
confidence: 99%
“…Apart from their predominant localization in the pancreas, GLP‐1 receptors (GLP‐1R) are also present in the brain regions including but not limited to the frontal cortex, hippocampus, amygdala, dorsal raphe, thalamus, hypothalamus, and the cerebellum. Also, caudal brainstem neurons protruding to the hippocampus, cortex, and hypothalamus have been found to secrete GLP‐1 (Merchenthaler et al., 1999; Yang et al., 2017). This extra‐pancreatic localization of the GLP‐1R suggests its prospect of employment in the combat against neurological diseases, including depression.…”
Section: Physiological Factors That Play Key Roles In the Comorbiditymentioning
confidence: 99%
“…Interestingly, growing evidence revealed that improving mitochondrial function with activation of PI3K/AKT and MEK/ERK pathways might tend to inhibit phosphorylation of c-Jun-NH2-terminal kinase (JNKs) and p38, the second and third major signaling cassettes in the MAPK pathway, which majorly respond to inflammatory and cellular stress to promote inflammation and cell death, in neuronal cells under many neurological conditions, both in vitro and in vivo studies [ 66 , 67 , 68 ]. Overall, MEK/ERK pathways have been reported to play a crucial role in protecting neuronal cells from death under hypoxia, global ischemia, epilepsy, status epilepticus, and Parkinson’s disease [ 33 , 63 , 68 , 69 ]. Therefore, following status epilepticus, endogenous activation of PGC-1α may regulate the VEGF/VEGFR2 (Flk-1) signaling pathway that triggers PI3K/AKT and MEK/ERK cascades and also promotes the cAMP-CREB signaling axis [ 45 , 69 ], which regulates the anti-apoptotic B-cell lymphoma-2 (Bcl-2) family, the expression of autophagy [ 63 ] and lysosomal genes, and further contributes to neuron survival mechanisms in hippocampal neuronal cells [ 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, MEK/ERK pathways have been reported to play a crucial role in protecting neuronal cells from death under hypoxia, global ischemia, epilepsy, status epilepticus, and Parkinson’s disease [ 33 , 63 , 68 , 69 ]. Therefore, following status epilepticus, endogenous activation of PGC-1α may regulate the VEGF/VEGFR2 (Flk-1) signaling pathway that triggers PI3K/AKT and MEK/ERK cascades and also promotes the cAMP-CREB signaling axis [ 45 , 69 ], which regulates the anti-apoptotic B-cell lymphoma-2 (Bcl-2) family, the expression of autophagy [ 63 ] and lysosomal genes, and further contributes to neuron survival mechanisms in hippocampal neuronal cells [ 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other pathways such as Akt/PKB, AMPk and ERK kinase activity are also enhanced by GLP-1 receptor activation (Sharma et al, 2013;Jalewa et al, 2016;Palleria et al, 2017). Genes that are activated include those relevant to energy utilization, for example, glucose uptake, mitochondrial function and replacement of damaged mitochondria (Lennox et al, 2014;Jalewa et al, 2016;Palleria et al, 2017); cell signaling that is linked to blocking apoptosis, for example, Bcl2 and Bax/BAD signaling and caspase activation (Baggio and Drucker, 2007;Kimura et al, 2009;Lupi et al, 2010); genes that control DNA repair (Yang et al, 2017), as well as control of chronic inflammation response in the brain that is observed in diabetics and that enhances oxidative stress (Parthsarathy and Holscher, 2013;Gault et al, 2015;Qin et al, 2016). In addition, autophagy, an important protective process that helps to eliminate cell debris that can become toxic if left to accumulate, is also enhanced and controlled by GLP-1 signaling (Jalewa et al, 2016;Panagaki et al, 2017).…”
Section: Second Messenger Signalling For Cell Growth Repair Energy mentioning
confidence: 99%